2021
DOI: 10.3390/ijms22063013
|View full text |Cite
|
Sign up to set email alerts
|

Central Apparatus, the Molecular Kickstarter of Ciliary and Flagellar Nanomachines

Abstract: Motile cilia and homologous organelles, the flagella, are an early evolutionarily invention, enabling primitive eukaryotic cells to survive and reproduce. In animals, cilia have undergone functional and structural speciation giving raise to typical motile cilia, motile nodal cilia, and sensory immotile cilia. In contrast to other cilia types, typical motile cilia are able to beat in complex, two-phase movements. Moreover, they contain many additional structures, including central apparatus, composed of two sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 148 publications
0
14
0
Order By: Relevance
“…The central microtubules, C1 and C2, are linked by so-called bridge and are a docking site for C1a-C1f and C2a-C2e complexes, called projections, and together form so-called central apparatus (CA). The CA projections differ in their size, architecture, protein composition, and likely function 3 , 4 . In consequence, the CA is asymmetric, which could be important for the generation of asymmetric waveforms.…”
Section: Introductionmentioning
confidence: 99%
“…The central microtubules, C1 and C2, are linked by so-called bridge and are a docking site for C1a-C1f and C2a-C2e complexes, called projections, and together form so-called central apparatus (CA). The CA projections differ in their size, architecture, protein composition, and likely function 3 , 4 . In consequence, the CA is asymmetric, which could be important for the generation of asymmetric waveforms.…”
Section: Introductionmentioning
confidence: 99%
“…On a deeper, subcellular level where structures have always been regarded as maximally conserved, the cilium reveals an unexpected heterogeneity of its central apparatus' protein composition: two recent proteomic studies of flagella in the Chlamydomonas green alga identified ~40 novel candidate proteins, of which only 15 have human orthologues, whereas the central apparatus' functionality and ultrastructural morphology remain universally stable (see Samsel et al [2021] for a review). Certainly, this evidence does not question the homology of eukaryotic cilium, although it does elicit that even critically important end‐function genes are prone to significant evolutionary change, which may not affect morphology or primary function.…”
Section: Implications Of Cell Type Theory In Evo‐devo Studiesmentioning
confidence: 99%
“…Two central microtubules (grey), together with associated complexes, a connecting bridge and projections (yellow), form a central apparatus. Main outer doublets (grey) complexes: outer dynein arms (ODAs, greenish), inner dynein arms (IDAs, purple), radial spokes (RSs, dark grey), nexin-dynein regulatory complex (N-DRC, orange); ( B ) Fragment of the outer doublet showing organization of ciliary complexes within a 96-nm outer doublet axonemal unit [ 9 , 10 ]. ODA (7K5B, PDB DOI: 10.2210/pdb7K5B/pdb [ 11 ]) and RS (7JTK, PDB DOI: 10.2210/pdb7JTK/pdb [ 12 ]) structures were obtained from a Protein Data Bank ( (accessed on 20 November 2022)).…”
Section: Figurementioning
confidence: 99%